Perlindungan Data Pribadi Konsumen dalam Penggunaan Aplikasi Pinjaman Online Ilegal - Zubir, Zubir; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of financial technology has driven the growth of online lending, yet the expansion of illegal online lending platforms has led to serious personal data violations. Unauthorized access to contacts, galleries, and locations is frequently followed by intimidating debt collection that degrades consumer dignity. This normative juridical research analyzes data protection regulations, types of violations, operators’ legal liabilities, and the effectiveness of victim protection in Indonesia. Utilizing statutory, conceptual, and case approaches, this study examines the Personal Data Protection Law (UU PDP), the ITE Law, and OJK regulations. The results indicate that although the UU PDP strengthens the normative legal framework, protection for victims remains sub-optimal due to illegal operators functioning outside the official network, weak law enforcement, and low digital literacy. Therefore, consumer protection requires cross-sector supervisory strengthening, aggressive law enforcement, and firmer personal data rights within the digital ecosystem.